Força de trabalho médica e regionalização da atenção à saúde do estado do Ceará - Melo, Ana Luisa Almeida (2016)
Imbalances between the availability and supply of medical professionals have affected access to health, making it important to understand the factors that determine the distribution of these professionals in health services. The state of Ceará, in the last five years, has expanded the Health Care Networks (RAS) in order to strengthen health regionalization. To do so, it is necessary to monitor the supply and distribution of the medical workforce. The objective was to study the medical workforce and its relations with the regionalization of Ceará. This is a case-study study with a mixed approach (qualitative and quantitative). Data collection was performed from August 2015 to May 2016, contemplating, as a field of research, the State Health System State of Ceará. As for the qualitative sources, open interviews were conducted with 13 key informants distributed among health, education and medical managers, as well as medical teachers. For the quantitative component, the secondary databases of the National Registry System of Health Establishments of the Ministry of Health - SCNES / MS were used; Of the Federal Council of Medicine; The Regional Council of Medicine of Ceará and the Unified System of Medical Residencies of Ceará. It had as analytical dimensions: availability and fixation of physicians in Ceará, medical training in the state of Ceará, implementation of RAS in Ceará and Regulation of access to health. Regarding the ethical aspect, this study complied with resolution 466, and has a number of opinion 137,055, approved by the Ethics Committee of the UFC. The results show that Ceará, according to the narratives studied, presents a greater concentration and fixation of the medical work force in the capital, Fortaleza, followed by the municipalities of the Cariri and Sobral macro-regions, and municipalities in the metropolitan region, which are important regional economic poles of State. We understand that the availability of physicians in health services is marked by professional turnover determined by factors such as: low frequency of public tenders and careers in the SUS, low remuneration, non-republican behaviors, guided by interests of local party politics, dispute between Public-private action. These factors have interfered in the fixation of physicians in the health services and that have accentuated the medical mobility in the state. Regarding medical education, we have seen an increase in the number of undergraduate courses in the state and, for medical residency, we do not yet have the necessary number of places in residency programs. We observe that the regulation of training has been guided by the market following particular interests. As for the implementation of SARs in the state, they are fragile, with fragmentation in management and health care. The regulation of access is one of the critical points of the health system of Ceará. Thus, we conclude that it is important to guarantee the medical professional in the provision of health services and services, as well as strengthening the integration of SARs in the state. This requires the state to continuously develop effective policies that ensure the provision, training and employment of these professionals, according to the health needs of the population.